Modernization of platform Schnabel car with a carrying capacity of 220 tons - Kebal, I. Y; Krasnoshchok, O. L (Science and Transport Progress, 2021)
Purpose. The article is aimed to calculate the strength of the element of the special design of the Schnabel car to increase the carrying capacity up to 250 tons, as well as consider the possibility of using special cars to transport the oversized cargo according to the strength calculation results of the span bolster of the Schnabel car. Methodology. A special design of the span bolster of the Schnabel car was developed, which allowed increasing the carrying capacity of the platform Schnabel car to 250 tons. SolidWorks CAD allowed testing the span bolster strength of the modernized Schnabel car. Findings. A review analysis of railway Schnabel cars has been performed. The possibility of testing the strength of the Schnabel car design details using modern SolidWorks CAD is considered. When loading the span bolster of the modernized Schnabel car with a compressive force of 2.5 MN, the stresses do not exceed the allowable, and the design has no weaknesses. The specialists of Design and Development Technological Bureau for the Design and Modernization of Rolling Stock, Track and Artificial Structures performed research and development for the production of a sixteen-axle platform Schnabel car with a capacity of up to 250 tons. Originality. The mathematical model of the modernized sixteen-axle platform Schnabel car with a loading capacity up to 250 t was further developed. The implementation of the mathematical model in SolidWorks CAD allowed testing the design for the strength of the Schnabel car. Practical value. The results of the work can be useful for the design departments for rolling stock design and relevant specialists. Modern CAD in some way simplifies the process of designing parts and assemblies of mechanisms, allowing one to test certain system parameters with high accuracy.